Studi Evaluasi Pemanfaatan Media Cetak Folder Pada Petani Dalam Budidaya Tanaman Cabe Di Kelurahan Rahandouna Kecamatan Poasia - Mardin Mardin; Tjandra Buana; Nunung Asri (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
The purpose of this study was to evaluate the use of folder print media for farmers in the cultivation of chilies. This research was conducted in Rahandouna Village, Poasia District, Kendari City. The determination of the research location was carried out deliberately (purposive sampling), with the consideration that in Rahandouna Village was the location for the development of chilli plants, as well as extension activities using folder print media. The research sample was determined by the census method, namely the chilli farmers who participated in extension activities through the printed media folder, totaling 10 farmers. The results showed that based on input evaluation, the media in the form of posters in extension activities was able to attract farmers to participate in counseling. The extension material presented is in accordance with the information needed by chilli farmers. Based on the process evaluation, extension workers are able to understand and adjust the methods, media and messages needed by farmers in extension activities. Meanwhile, in the output evaluation, after participating in the counseling, chilli farmers were very interested in applying the message or material content delivered by the extension agent